Difference in flowering time can initiate speciation of nocturnally flowering species. (7th April 2015) - Matsumoto, Tomotaka; Yasumoto, Akiko A; Nitta, Kozue; Hirota, Shun K; Yahara, Tetsukazu; Tachida, Hidenori
Abstract: Isolation mechanisms that prevent gene flow between populations prezygotically play important roles in achieving speciation. In flowering plants, the nighttime flowering system provides a mechanism for isolation from diurnally flowering species. Although this system has long been of interest in evolutionary biology, the evolutionary process leading to this system has yet to be elucidated because of the lack of good model species. However, the genetic mechanisms underlying the differences in flowering times and the traits that attract pollinators between a pair of diurnally and nocturnally flowering species have recently been identified in a few cases. This identification enables us to build a realistic model for theoretically studying the evolution of a nocturnally flowering species. In this study, based on previous experimental data, we assumed a model in which two loci control the flowering time and one locus determines a trait that attracts pollinators. Using this model, we evaluated the possibility of the evolution of a nocturnally flowering species from a diurnally flowering ancestor through simulations. We found that a newly emerging nighttime flowering flower exhibited a sufficiently high fitness, and the evolution of a nocturnally flowering species from a diurnally flowering species could be achieved when hybrid viability was intermediate to low, even in a completely sympatric situation. Our results suggest that the difference in flowering time can act as a magic trait that induces both natural selection and assortative mating and would play an important role in speciation between diurnally and nocturnally flowering species pairs. Highlights: We simulated the evolution of the nocturnally flowering species. We included genetic model which is estimated from empirical studies. We examined the probability of the evolution under several parameter sets. As the result, the evolution occurred in relatively wide parameter range. Our result suggested the effect of the flowering time as a magic trait of speciation.